Approaching Freshet beneath Landfast Ice in Kugmallit Bay on the Canadian Arctic Shelf: Evidence from Sensor and Ground Truth Data - Walker, Tony R.; Grant, Jon; Jarvis, Peter (ARCTIC, 2009)
The Mackenzie River is the largest river in the North American Arctic. Its huge freshwater and sediment load impacts the Canadian Beaufort Shelf, transporting large quantities of sediment and associated organic carbon into the Arctic Ocean. The majority of this sediment transport occurs during the freshet peak flow season (May to June). Mackenzie River-Arctic Ocean coupling has been widely studied during open water seasons, but has rarely been investigated in shallow water under landfast ice in Kugmallit Bay with field-based surveys, except for those using remote sensing. We observed and measured sedimentation rates (51 g m-2 d-1) and the concentrations of chlorophyll a (mean 2.2 ?g L-1) and suspended particulate matter (8.5 mg L-1) and determined the sediment characteristics during early spring, before the breakup of landfast ice in Kugmallit Bay. We then compared these results with comparable data collected from the same site the previous summer. Comparison of organic quality in seston and trapped material demonstrated substantial seasonal differences. The subtle changes in biological and oceanographic variables beneath landfast ice that we measured using sensors and field sampling techniques suggest the onset of a spring melt occurring hundreds of kilometres farther south in the Mackenzie Basin. Le fleuve Mackenzie est le plus grand fleuve de l’Arctique nord-américain. Son énorme bassin d’eau douce et sa masse de sédiments ont des effets sur la plateforme externe de la mer de Beaufort canadienne, transportant ainsi de grandes quantités de sédiments et de carbone organique associé dans l’océan Arctique. La plus grande partie du transport des sédiments se produit pendant la saison haute d’écoulement du courant d’eau douce dans la mer (de mai à juin). Même si le couplage du fleuve Mackenzie et de l’océan Arctique a fait l’objet d’études approfondies durant les saisons d’eau libre, il a rarement été étudié en eau peu profonde sous la banquise de la baie Kugmallit au moyen d’études sur le terrain, sauf dans le ...